Exploring The Impact of Guided Inquiry Learning with a Scientific Approach on Mathematical Conceptual Understanding - Isran, Dodi; Haji, Saleh; Sumardi, Hari; Syafri, Fatrima Santri (Universitas Ma'arif Lampung, 2024)
This research explores the impact of Guided Inquiry Learning-oriented learning with a scientific approach on understanding mathematical concepts of PGMI UIN Fatmawati Sukarno Bengkulu students. The research design uses an experimental method with an experimental group and a control group. The results of the analysis show that students who were taught using Guided Inquiry Learning-oriented learning experienced a significant increase in understanding mathematical concepts compared to learning without a Guided Inquiry Learning orientation, even though both used a scientific approach. A significant value of less than 0.05 in a statistical test indicates that the difference can be considered statistically significant. However, the results of further analysis showed that there was no significant difference in increasing understanding of mathematical concepts between classes that used the Scientific Approach and the control group in two particular classes (Class=2 and Class=3). A P-value greater than 0.05 in statistical analysis indicates that the results are not statistically significant. Thus, although there was a significant increase in understanding of mathematical concepts in the group that implemented Guided Inquiry Learning-oriented learning, this research also showed that there was no significant difference in this increase between this group and the control group in two particular classes. These results provide further understanding about the effectiveness of certain learning methods in improving students' understanding of mathematical concepts.